MODEL ROLE PLAYING DALAM MENANAMKAN SIKAP TOLERANSI SISWA SEKOLAH DASAR - Tya Hanifah Firdiana; Endang Wahyudiana; Tunjungsari Sekaringtyas (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research discusses the effectiveness of the role playing learning model in instilling tolerance in elementary school students. Tolerance is an important value that needs to be formed early on to create harmony in a pluralistic society. However, conventional learning methods are often ineffective in internalizing this value deeply. Using the literature study method, this research analyzes various scientific sources related to the application of role playing as an active learning method that provides direct experience to students in understanding and appreciating tolerance. The results show that role playing can improve students' cognitive understanding and affective aspects, such as empathy, self-confidence, and social skills. The integration of local wisdom also enriches the learning context so that the value of tolerance becomes more meaningful and relevant. The role of teachers and a supportive school environment are important factors in the successful implementation of this method. This study concludes that the role playing model is effective to be developed in character education at the elementary school level.